Economic Pressure, Livelihood Strategy, and Family Well-being in Cimanuk Watershed, Garut and Indramayu, West Java, Indonesia - Hamira Sabania; Hartoyo Hartoyo (Journal of Family Sciences, 2016)
The objective of this study is to analyze economic pressure, livelihood strategy, and well-being of families in Cimanuk Watershed. This study used a cross-sectional study design. As many as 72 samples of lower middle class families (determined by Poverty Line of BPS 2013) who have toddler and school age children were chosen puposively. This study was conducted in Garut District and Indramayu District. The results showed that inspite of being in poverty, only one out of three families felt highly economic pressure, and one out of ten families perceived poorly well-being. Family economic pressure was affected by the region difference, education level of father, and ownership of financial capital. Meanwhile, family well-being was affected by the education level of the father, financial capital, social capital, access to the environment, economic pressure, and livelihood diversification. Livelihood diversification is the strategy that most poor families did in Cimanuk Watershed. Livelihood diversification of families was affected by the age of the wife, expenditure per capita, social capital, and access to the environment.